Three-Dimensional Culture of Ameloblast-Originated HAT-7 Cells for Functional Modeling of Defective Tooth Enamel Formation - Földes, Anna; Sang-Ngoen, Thanyaporn; Kádár, Kristóf; Rácz, Róbert; Zsembery, Ákos; DenBesten, Pamela; Steward, Martin C.; Varga, Gábor (Frontiers in Pharmacology, 2021)
Background: Amelogenesis, the formation of dental enamel, is well understood at the histomorphological level but the underlying molecular mechanisms are poorly characterized. Ameloblasts secrete enamel matrix proteins and Ca2+, and also regulate extracellular pH as the formation of hydroxyapatite crystals generates large quantities of protons. Genetic or environmental impairment of transport and regulatory processes (e.g. dental fluorosis) leads to the development of enamel defects such as hypomineralization. Aims: Our aims were to optimize the culture conditions for the three-dimensional growth of ameloblast-derived HAT-7 cells and to test the effects of fluoride exposure on HAT-7 spheroid formation. Methods: To generate 3D HAT-7 structures, cells were dispersed and plated within a Matrigel extracellular matrix scaffold and incubated in three different culture media. Spheroid formation was then monitored over a two-week period. Ion transporter and tight-junction protein expression was investigated by RT-qPCR. Intracellular Ca2+ and pH changes were measured by microfluorometry using the fluorescent dyes fura-2 and BCECF. Results: A combination of Hepato-STIM epithelial cell differentiation medium and Matrigel induced the expansion and formation of 3D HAT-7 spheroids. The cells retained their epithelial cell morphology and continued to express both ameloblast-specific and ion transport-specific marker genes. Furthermore, like two-dimensional HAT-7 monolayers, the HAT-7 spheroids were able to regulate their intracellular pH and to show intracellular calcium responses to extracellular stimulation. Finally, we demonstrated that HAT-7 spheroids may serve as a disease model for studying the effects of fluoride exposure during amelogenesis. Conclusion: In conclusion, HAT-7 cells cultivated within a Matrigel extracellular matrix form three-dimensional, multi-cellular, spheroidal structures that retain their functional capacity for pH regulation and intracellular Ca2+ signaling. This new 3D model will allow us to gain a better understanding of the molecular mechanisms involved in amelogenesis, not only in health but also in disorders of enamel formation, such as those resulting from fluoride exposure.